A double point mutation at residues Ile14 and Val15 of Bcl‐2 uncovers a role for the BH4 domain in both protein stability and function. (2nd December 2017) - Monaco, Giovanni; La Rovere, Rita; Karamanou, Spyridoula; Welkenhuyzen, Kirsten; Ivanova, Hristina; Vandermarliere, Elien; Di Martile, Marta; Del Bufalo, Donatella; De Smedt, Humbert; Parys, Jan B.; Economou, Anastassios; Bultynck, Geert
Abstract : B‐cell lymphoma 2 (Bcl‐2) protein is the archetype apoptosis suppressor protein. The N‐terminal Bcl‐2‐homology 4 (BH4) domain of Bcl‐2 is required for the antiapoptotic function of this protein at the mitochondria and endoplasmic reticulum (ER). The involvement of the BH4 domain in Bcl‐2′s antiapoptotic functions has been proposed based on Gly‐based substitutions of the Ile14/Val15 amino acids, two hydrophobic residues located in the center of Bcl‐2′s BH4 domain. Following this strategy, we recently showed that a BH4‐domain‐derived peptide in which Ile14 and Val15 have been replaced by Gly residues, was unable to dampen proapoptotic Ca 2+ ‐release events from the ER. Here, we investigated the impact of these mutations on the overall structure, stability, and function of full‐length Bcl‐2 as a regulator of Ca 2+ signaling and cell death. Our results indicate that full‐length Bcl‐2 Ile14Gly/Val15Gly, in contrast to wild‐type Bcl‐2, (a) displayed severely reduced structural stability and a shortened protein half‐life; (b) failed to interact with Bcl‐2‐associated X protein (BAX), to inhibit the inositol 1, 4, 5‐trisphosphate receptor (IP3 R) and to protect against Ca 2+ ‐mediated apoptosis. We conclude that the hydrophobic face of Bcl‐2′s BH4 domain (Ile14, Val15) is an important structural regulatory element by affecting protein stability and turnover, thereby likely reducing Bcl‐2′s ability to modulate the function of its targets, like IP3 R and BAX. Therefore, Bcl‐2 structure/function studies require pre‐emptive and reliable determination of protein stability upon introduction of point mutations at the level of the BH4 domain. Abstract : Hydrophobic‐core residues (Val14 and Ile15) of the antiapoptotic protein Bcl‐2, which are located in the center of the BH4 domain, critically contribute to the structural stability of the protein and in turn to Bcl‐2's ability to counteract BAX‐ and IP3 R‐proapoptotic functions. Therefore, BH4‐directed mutagenesis studies should accurately evaluate whether any observed alteration in Bcl‐2‐protein function is attributable to a difference in the overall protein stability before implying a local effect on BH4‐domain activity.